Decontamination effects of the corona discharge with plane to bent needle configuration - Bujaček, K.; Fantova, V.; Kříha, V. (Вопросы атомной науки и техники, 2012)
The dependency of the inhibition zone size on the needle geometry and angle between needle and plane in plane to needle electrode configuration was studied. Needles bent at angles from 0° (straight one) to 90° were used to study both negative and positive corona discharge treatment of the surface contaminated with Candida albicans yeasts.Inhibition zones shape and size changes were studied for positive and negative corona discharge. Ellipsoidal shape was characteristic for all treated samples in case of positive corona treatment, while the three-segment shape was observed for higher angles in case of negative corona discharge. Исследовалась зависимость размеров пораженной зоны от геометрии иглы, а так же от угла между иголочным и плоскостным электродами. Иглы согнутые под углами от 0 (прямая игла) до 90 градусов использовались для изучения влияния положительного и отрицательного коронного разряда на поверхность загрязненную дрожжами рода Candida albicans. Эллиптическая форма была характерна для всех образцов обработанных положительным разрядом. В случае использования отрицательной короны, зона состояла из трех сегментов. Это явление можно было особенно ясно наблюдать при использовании больших углов изгиба иголочного электрода. Досліджувалась залежність розмірів ураженої зони від геометрії голки, а також від кута між голковим та площинним електродом. Голки зігнуті під кутами від 0 (пряма голка) до 90 градусів використовувались для вивчення впливу позитивного та негативного коронного розряду на поверхню, забруднену дріжжами роду Candida albicans. Еліптична форма була характерна для всіх зразків, оброблених позитивним розрядом. При використанні від'ємної корони зона складалась з трьох сегментів. Це явище добре спостерігалося під час використання великих кутів вигину голкового електрода.